Alcibiades's Epiphanic Experience in Plato's Symposium. - Petraki, Zacharoula (Illinois Classical Studies)
In Plato's Symposium , Alcibiades resorts to the imagery of art and describes the Socratic virtues in terms of "divine statues." In this paper, I argue that Plato makes Alcibiades use the poetics of divine salvific and erotic epiphany in order to describe his (quasi) epiphanic experience at the sight of Socrates at Potidaia, Delion, and Agathon's house. First, I offer a brief account of scholarly views on this imagery and of my own contribution. Then, I discuss Alcibiades's Bacchic experience with Socrates qua Silenus, and I examine those passages in which Plato turns traditional epiphanic language to his own ends.